2016
DOI: 10.3390/atmos7050066
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Environmental Characteristics for the Tropical Cyclone Genesis in the Indian Ocean during the CINDY2011/DYNAMO Field Experiment

Abstract: This study investigated the seasonal environmental characteristics for tropical cyclone genesis (TCG) over the Indian Ocean during the Cooperative Indian Ocean Experiment on Intraseasonal Variability in the Year 2011 and the Dynamics of the Madden-Julian Oscillation (MJO) (CINDY2011/DYNAMO) field experiment and compare them with long-term climatological features. It was found that the spatial pattern of an empirical environmental index for TCG over the tropical Indian Ocean in 2011 is very similar to the featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The present study hypothesized that water-vapor content distribution can affect TC tracks, and examined the hypothesis through analyzing the Severe Typhoon Hato (2017) using the Weather Research and Forecasting (WRF) Model (Skamarock et al 2008). Our previous study showed that the intensification of Hato was significantly affected by environmental water vapor (Wu et al 2020).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present study hypothesized that water-vapor content distribution can affect TC tracks, and examined the hypothesis through analyzing the Severe Typhoon Hato (2017) using the Weather Research and Forecasting (WRF) Model (Skamarock et al 2008). Our previous study showed that the intensification of Hato was significantly affected by environmental water vapor (Wu et al 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Xu et al (2013) identified that TCs, particularly some severe ones, exhibited the trend of making landfalls toward warmer land in China during 1960-2009 because a warmer surface provides moisture and energy to TCs. TCs typically intensify when they pass over warmer surface areas or encounter favorable environmental conditions in the lower atmosphere (Wang et al 2001;Miglietta et al 2011;Rai and Pattnaik 2018), particularly higher water-vapor content (WVC) Krall and Cottom 2012;Tsuboi et al 2016;Khain et al 2016). Herbener et al (2014) reported that moist aerosols can initiate interactions between cloud microphysics and storm dynamics via latent heat release, thus leading to TC intensification.…”
Section: Introductionmentioning
confidence: 99%
“…8,18,21 A significant focus has been placed on determining factors influencing the inter-annual variability, both in the number of storms and their geographic location within the ocean basin, highlighting the significant role of El Niño Southern Oscillation, Quasi-Biennial Oscillation, Indian Ocean Dipole and Madden-Julian Oscillation. 8,[19][20][21][22] Because of the socio-economic vulnerability within the region, research on South Indian Ocean tropical cyclones has included the considerable infrastructural and economic costs associated with storm damage. 18,23,24 This study reflects on the emergence of tropical cyclones in the IBTrACS record for the South Indian Ocean in 1994, and the changing dynamics of these storms over the past two decades, including changes in the number of CAT5 storms, the latitudinal positions of the storms, and the underlying sea surface temperatures as drivers of cyclogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MJO is a large-scale cluster of convective clouds in the tropics Julian, 1971, 1972;Zhang, 2005) and sometimes affects the generation and evolution of tropical cyclones by changing the atmospheric conditions favorable for tropical cyclogenesis (Liebmann et al, 1994;Bessafi and Wheeler, 2006;Kim et al, 2008;Camargo et al, 2009;Chand and Walsh, 2010;Kikuchi and Wang, 2010;Huang et al, 2011;Yanase et al, 2012;Klotzbach and Blake, 2013;Klotzbach, 2014;Tsuboi and Takemi, 2014). With the use of an index that describes the potential for tropical cyclogenesis (Murakami et al, 2011), it was found that the increase in humidity is an important condition favorable for the generation of tropical cyclones in the Indian Ocean during the active periods of MJO (Tsuboi and Takemi, 2004;Tsuboi et al, 2016). Klotzbach and Blake (2013) indicated that during the convectively active phase of the MJO over the eastern and central tropical Pacific the north-central Pacific tends to have more TCs and the convectively active phase of MJO is responsible for north-central Pacific TCs that experience rapid intensification.…”
Section: Introductionmentioning
confidence: 99%